Implementation of Character Education in Elementary Schools through an Ecological Approach - Elliani, Fetti; Mahmud, Salami; Walidin, Warul (Journal of Indonesian Primary School, 2024)
The aim of this research is to evaluate how to implement character education in elementary schools using an ecological approach. The approach applied is qualitative research. Data was obtained from observation, interviews and document research. Research finds that the best way to implement character education is to create a conducive school environment, integrate character values in learning, involve parents and the community, utilize the natural environment, and develop character-based extracurricular programs. By considering the relationship between students and the surrounding environment, the implementation of character education in elementary schools can be effective through an ecological approach. The results of the study show that the implementation of character education using an ecological approach in elementary schools provides a comprehensive and contextual framework. This method allows schools to create a comprehensive learning environment, where characters are not only taught in theory but also practiced in various everyday situations by students.